Inovasi Produk Kriya Keramik dan Tekstil Berbasis Teknologi Digital Untuk Pemberdayaan Masyarakat - Cahyaningrum, Yuniana; Nikita Noviyanti; Atika Nur Rohmah; Ghina Legislativa Amrullah (Sinesia : Jurnal Pengabdian Masyarakat, 2026)
The development of digital technology provides significant opportunities for the development of the arts and crafts sector, particularly in enhancing the aesthetic and economic value of products. This community service activity aims to develop innovative ceramic and textile-based craft products through the use of digital technology to increase the capacity, creativity, and competitiveness of the community, particularly micro, small, and medium enterprises (MSMEs). The main problems faced by partners include limitations in product diversification, low utilization of technology in the design and marketing process, and the lack of added value to the resulting craft products. The activity implementation method includes the stages of identifying the potential and needs of partners, digital-based product design training, mentoring innovative production processes, and strengthening marketing strategies based on digital platforms. The technologies applied include digital graphic design, QR Code integration as a product information medium, and the introduction of the Augmented Reality concept to increase the interactive and educational value of products. The results of the activity show an increase in partners' skills in developing more innovative, functional, and aesthetically valuable craft product designs. The resulting products include decorative ceramics based on local motifs, multifunctional textile products, and ceramic-textile combination crafts with an environmentally friendly approach. In addition, there has been an increase in partners' understanding of the importance of branding, product storytelling, and digital marketing. The impact of this activity not only increases the economic value of products but also strengthens local cultural identity and encourages digital transformation in the craft sector. Thus, digital technology-based craft product innovation can be an effective strategy for sustainable community empowerment.